Innovative Team-Learning Project for Undergraduate Pathology Education. (24th June 2021) - Arries, Cade; Williams, Sarah; Wallschlager, Andrew; Jernberg, Chelsey; Powell, Deborah
At the University of Minnesota, Twin Cities Campus, we have completed our seventh year of an innovative small group learning activity in an undergraduate medical school course. The purpose of the Independent Study Project has been to expose students to the process of making a pathologic diagnosis in a team-based learning format. In the Independent Study Project groups of 3 or 4 students work together to determine a diagnosis on an assigned unknown case, and then compose a 3- to 5-page paper focusing on the disease entity and the basic science underlying the disease. This project emphasizes team-based learning and illustrates the relationship and integration of pathology with clinical medicine. Professionalism is also emphasized with students evaluating and providing feedback to fellow group members. Over time, the format has become more web based with all of the cases available online with digitally scanned microscopic slides and images. Overall, the Independent Study Project has been well received by both faculty members and students.